Residential Construction Academy: Basic Principles for Construction, 5th Edition - Mark Huth (Cengage Learning, 2019)
Prepare for a successful career in the building trades with RESIDENTIAL CONSTRUCTION ACADEMY: BASIC PRINCIPLES FOR CONSTRUCTION, Fifth Edition. This reader-friendly, highly visual, full-color book was created in partnership with the Home Builders Institute (HBI) and based on National Skill Standards for residential construction, so you can be confident you'll gain the knowledge and skills you need to succeed. The new edition includes updates to give you the latest information on today's industry standards, current technology and techniques, and practices you'll likely encounter on the job. You'll also learn essential ideas and skills to help you launch and grow your career, including work ethics, safety procedures, construction mathematics, communications, print reading, and common tools.